Pancasila Values in the Business Event Against Entrepreneurial Attitudes - Monalisa, Monalisa (Universitas Sebelas Maret, 2021)
This study examines the importance of Pancasila values in the field of entrepreneurship and the method used in this research is the case study method. Pancasila is the ideology of the Indonesian nation which includes important values to be applied in the world of entrepreneurship. In a business event, such as the simplypopupmarket event which was held during the Covid-19 pandemic, namely the Nummy Local brand (Hanum Mega), Hair Repair (Audi Marisa) and other brands without being based on Pancasila values, business events will easily split. An entrepreneur or brand owner must be based on the values of Pancasila. When an event is held by an event program owner, a brand owner not only sees other brands or other booths as a threat to himself, but sees that the booth is his business partner so that all local products can compete together without destroying national unity and unity. . As was done by Audi Marisa (Hair Repair) as well as public figures who visited each booth at the event. at the same time buying other products to support local products to remain victorious in Indonesia. A good entrepreneur is a person who struggles based on the values of Pancasila.